2016
DOI: 10.1021/acs.analchem.5b04010
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing a Key Aptamer Structure-Switching Mechanism for the Ultrahigh Frequency Detection of Cocaine

Abstract: Aptasensing of small molecules remains a challenge as detection often requires the use of labels or signal amplification methodologies, resulting in both difficult-to-prepare sensor platforms and multistep, complex assays. Furthermore, many aptasensors rely on the binding mechanism or structural changes associated with target capture by the aptameric probe, resulting in a detection scheme customized to each aptamer. It is in this context that we report herein a sensitive cocaine aptasensor that offers both rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 75 publications
(162 reference statements)
0
16
0
Order By: Relevance
“…As candidates for replacing antibodies, aptamers possess advantages of relatively simple synthetic preparation, low batch-to-batch variability, facile modification, low immunogenicity, and structural robustness [7][8][9][10]. In addition, it has been widely reported that aptamers have unique properties of conformational change/adaptive binding, making them more versatile as molecular recognition elements [11][12][13][14][15]. Thus, they have been applied in diagnosis, biosensing, bio-imaging, drug delivery, and drug discovery [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…As candidates for replacing antibodies, aptamers possess advantages of relatively simple synthetic preparation, low batch-to-batch variability, facile modification, low immunogenicity, and structural robustness [7][8][9][10]. In addition, it has been widely reported that aptamers have unique properties of conformational change/adaptive binding, making them more versatile as molecular recognition elements [11][12][13][14][15]. Thus, they have been applied in diagnosis, biosensing, bio-imaging, drug delivery, and drug discovery [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The sensing interface consists of a S-(11-trichlorosilyl-undecanyl) benzenethiosulfonate (BTS) adlayer-coated quartz disc onto which a structure-switching cocaine aptamer was immobilized, completing the preparation of the MN4 cocaine aptamer with an apparent Kd of 45 ± 12 μM and limit of detection of 0.9 μM. The same group developed an MN6 cocaine aptasensor using an EMPAS platform that had apparent Kd of 27 ± 6 and a 0.3 μM detection limit [54].…”
Section: Acoustic Aptasensorsmentioning
confidence: 99%
“…The PHASA combines the advantages of the aptamer adaptive binding assay [5,6,[10][11][12] and fluorescence-photochrome assay based on stilbene photoisomerisation [13][14][15][16][17][18]. The PHASA relies on the photoisomerisation of a fluorescent trans-stilbene to a non-fluorescent cis-stilbene -an intramolecular process taking less than several nanoseconds.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…By rearranging Equation [12], the concentration of the formed ligand-aptamer complex can then be expressed as:…”
Section: Calculation Of the Analyte Concentrationmentioning
confidence: 99%